Cyst-theca relationship and phylogenetic positions of Scrippsiella plana sp. nov. and S. spinifera (Peridiniales, Dinophyceae). Issue 2 (2nd April 2016) - Luo, Zhaohe; Mertens, Kenneth Neil; Bagheri, Siamak; Aydin, Hilal; Takano, Yoshihito; Matsuoka, Kazumi; McCarthy, Francine M.G.; Gu, Haifeng
Abstract: Species belonging to the dinophyte genus Scrippsiella are frequently reported in marine waters, but information on their distribution in brackish environments is limited. Here we describe a new species, S. plana, through incubation of non-calcified cysts from sediments collected in the South China Sea and Caspian Sea. The vegetative cells consist of a conical epitheca and a rounded hypotheca with the plate formula of Po, X, 4′, 3a, 7′′, 5C+t, 5S, 5′′′, 2′′′′. It differs from other Scrippsiella species by its flattened body in dorsoventral view and a small first anterior intercalary (1a) plate (half the size of plate 3a). Scrippsiella plana strains from the South China Sea and Caspian Sea share identical internal transcribed spacer (ITS) sequences, and show phenotypic plasticity and local adaptation in growth rate at various salinities, consistent with the environments in which they originated. In addition, two strains of S. spinifera were obtained by incubating ellipsoid cysts with calcareous spines from sediments collected along the Turkish and Hawaiian coast. They also share identical ITS sequences and differ from Duboscquodinium collinii (a parasite of tintinnids) only at two base pair positions (in the ITS2 region). Molecular phylogeny based on ITS and large subunit ribosomal DNA (LSU rDNA) sequences revealed that S. plana was nested within the Calciodinellum (CAL) clade and S. spinifera within the S. trochoidea (STR) clade. The phylogenetic position of ' Peridinium ' wisconsinense is reported for the first time, which supports multiple transitions of the Peridiniales to freshwater.